The Effects of Amofer Palm Oil Waste-based Complete Feed to Blood Profiles and Liver Function on Local Sheep - Hamdi Mayulu; S Sunarso; C. Imam Sutrisno; S Sumarsono (International Journal of Science and Engineering, 2012)
Amoniation-Fermentation (amofer) technology should be conducted in order to improve the low quality of by product produced from palm oil plantations and mills (palm oil waste) which is used for constituent of feed ingredients in complete feed (CF). This technology also reforms the feed material into edible form. Before broadly applicable, it must be ensured that the feed does not have toxic effects on livestock. This research was peformed to evaluate the effects of amofer palm oil waste-based CF to blood profile and liver function on local sheep. Completely Randomly Design (CRD) was used with 4 treaments and 4 replications. The observed variables were the levels of hemoglobin, hematocrit, blood glucose, ALT and AST was analyzed by ANOVA. The average value of blood glucose levels at T1= 80.68 mg/dl, T2=79.08 mg/dl, T3=81.18 mg/dl and T4=73.70 mg/dl. The average value of hemoglobin levels at T1=10.80 g/dl, T2=10.30 g/dl, T3=11.23 g/dl and T4=10.25 g/dl. The average value of hematocrit levels at T1=31.00%, T2=31.00%, T3=33.75% and T4=30%. The average value of ALT levels at T1=17.90 ml, T2=13.83 ml, T3=18.75 ml and, T4=13.40 ml. The average value of AST level at T1=106.20 ml, T2=88.98 ml, T3=104.40 ml and T4=91.25 ml. There was no significant difference among four treatments (p>0.05). The administration CF did not cause hematological disorders which showed by the blood profiles and liver function were in normal range, so that suggested the CF was appropriate and safe for local sheep. [Keywords––amofer, complete feed, hemoglobin, hematocrit, glucose, liver function]